Implementasi Proses Manufaktur Pembangkit Listrik Bertenaga Angin Dan Surya Di Pesisir Pantai Matras - Kevin, Cristian; Rollastin, Boy; Husman, Husman (Jurnal Inovasi Teknologi Terapan, 2023)
Indonesia is a country rich in natural resources and natural resources. These natural resources can be in the form of wind and solar heat, wind and solar heat can be utilized as an alternative to power generation with the type of power generator in the form of wind turbines and solar panels. In certain areas there are still many that require a supply of electric power, for example in the Turun Aban Beach area. At that location there is no electricity supply at all. Meanwhile, the fishermen at the Turun Aban Beach location often carry out the process of transporting their catch at night. Therefore, to meet the needs of these fishermen, they can use alternative power generators in the form of wind turbines and solar panels. Coastal areas have great potential for wind speed and solar heat. This research examines the process of implementing wind and solar power generators that will be used as alternative lighting for fishermen on the Turun Aban Beach, Matras Bangka Village. The process of making the tool will be carried out at the PolmanBabel Mechanical Workshop. Making this tool will go through several stages such as cutting the frame material, welding, turning and also assembling the electrical circuit on the tool.